2015
DOI: 10.5897/ajar2014.9132
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and economic evaluation of the N and P response of bread wheat grown in the moist and humid midhighland vertisols areas of Arsi zone, Ethiopia

Abstract: Field experiment was conducted in 2012 and 2013 in three districts of Arsi zone, Oromia region, Ethiopia to evaluate the response of bread wheat cultivar "Damphe" under highland vertisols to treatments consisting of 20 factorial combinations of five N rates from urea and four P205 rates from triple super phosphate (TSP). The treatments were laid out in RCBD, replicated three times. All data were subjected to analysis of variance using SAS 9.0 Statistical Analysis Software. Treatment effects on the average grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…0.27% with 1% increase in N applied (Table 3). Earlier studies also identified N fertilisation as a key determinant of wheat yields in Ethiopia (Habte et al 2014;Tanner et al 1993) but further research should investigate whether increasing N rates is economically viable for smallholders (cf. van Dijk et al 2017).…”
Section: Production Frontier and Yield Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…0.27% with 1% increase in N applied (Table 3). Earlier studies also identified N fertilisation as a key determinant of wheat yields in Ethiopia (Habte et al 2014;Tanner et al 1993) but further research should investigate whether increasing N rates is economically viable for smallholders (cf. van Dijk et al 2017).…”
Section: Production Frontier and Yield Variabilitymentioning
confidence: 99%
“…Previous research concluded wheat yield gaps in West Arsi, one of the wheat belts in Ethiopia, can be largely attributed to technology yield gaps (Silva et al 2019a). This means that technologies currently used by farmers do not reach agronomic best practices and that considerably more and better use of inputs is needed if wheat yield gaps are to be narrowed (Habte et al 2014;Tanner et al 1993). Competition for labour during sowing, weeding, and harvesting was also observed in this administrative zone, as labour peaks for other cereal and legume crops overlap with labour peaks for wheat.…”
Section: Introductionmentioning
confidence: 99%
“…The average wheat productivity is 3.0 t ha -1 (Anonymous, 2022) which is low as compared to that of the world Fisseha et al (2020) reported 61%, 55%, and 46% wheat yield gap compared to the actual yield on the research station, farmers' plot, and potential yield in the highland areas of the country, respectively. The yield gap observed could be attributed to the Presence of significant GEI (genotype by environment interaction) Gadisa et al, 2021;Verma and Singh, 2021); lack of high yielding and stable varieties suitable to diverse agro-ecologies; biotic stresses (Olivera et al, 2015;Singh et al, 2015;Tolemariam et al, 2018); abiotic stresses; poor cultural practices; monocropping and socio-economic (Habte et al, 2014;Ayele et al, 2008;Hodson et al, 2020;Negash et al, 2022;Abate, 2023). Wheat diseases such as yellow rust (Puccinia striifirmis f.sp tritici) and stem rust (P. graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Soil acidity and depletion of essential plant nutrients are among the major abiotic stresses that constrained wheat productivity in Ethiopia in general and in the study area in particular [ [11] , [12] , [13] , [14] , [15] , [16] ]. About 43 % of the cultivable land in Ethiopia is affected by soil acidity [ 12 ], of which about 28 % is categorized under strongly acidic (pH < 5.5) (11).…”
Section: Introductionmentioning
confidence: 99%